Enseñanza y Aprendizaje del Inglés: A través de las TICs en las escuelas normales en México/Recrea - Morales, José; Scyner, Gareth; Mendoza, María (CIEX JOURNAL, 2020)
This article investigates the teaching experiences made during the course of the year 2019 at the Bachelor of Primary Education at the Benemérito Instituto Normal del Estado (BINE) in Puebla, Mexico. The study addresses the following questions: How are teaching skills developed to improve the level of English teaching? How does the use of ICT impact the learning of English in students? In addition, the article also aims to characterize the teaching and learning of English from the foundations of complex thinking, the development of competences facilitated through the use of Learning Technologies and Knowledge (LTK), looking at an Instructional model within a constructivist approach. Finally, the research article considers the qualitative paradigm within an action research design, and applies observation and analysis guidelines for course planning. The preliminary results for teaching as a result of classroom intervention within this framework is presented.